Enterprise Resource Planning (ERP) Has an Impact on the Management Control System and the Work of Accountants: Examining the impact of ERP on management control system and accountants' roles in Malaysian enterprises (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Information and communication technologies (ICTs) are transforming not just people's lives but also corporate operations. One example of how technology transforms company from a labor-intensive to a machine-intensive process while improving organisational control is enterprise resource planning (ERP). The goals of this study are to assess the impact of ERP system deployment on the management control system and to identify changes in accountants' functions as a result of ERP system implementation. Two enterprises in Malaysia were chosen, one in construction and the other in property development, and triangulated data-collection approaches of observation, document analysis, and interviews were used. The ERP system, according to this study, is a good instrument for a formal management control system since it helps organisations uncover waste as soon as feasible. In terms of accountants' roles, the ERP has substantially enhanced their job because they can now devote more time to financial analysis and decision-making rather than data input.